Risk Factors Influencing Tolerance and Clinical Features of Food Protein–induced Allergic Proctocolitis. Issue 5 (May 2020) - Buyuktiryaki, Betul; Kulhas Celik, Ilknur; Erdem, Semiha B.; Capanoglu, Murat; Civelek, Ersoy; Guc, Belgin Usta; Guvenir, Hakan; Cakir, Murat; Dibek Misirlioglu, Emine; Akcal, Omer; Volkan, Burcu; Toyran, Muge; et al.
ABSTRACT: Objective: Continued progress in our understanding of the food protein–induced allergic proctocolitis (FPIAP) will provide the development of diagnostic tests and treatments. We aimed to identify precisely the clinical features and natural course of the disease in a large group of patients. Also, we investigated the predicting risk factors for persistent course since influencing parameters has not yet been established. Methods: Infants who were admitted with rectal bleeding and had a diagnosis of food protein–induced allergic proctocolitis in 5 different allergy or gastroenterology outpatient clinics were enrolled. Clinical features, laboratory tests, and prognosis were evaluated. Risk factors for persistent course were determined by logistic regression analyses. Results: Among the 257 infants, 50.2% (n = 129) were girls and cow's milk (99.2%) was the most common trigger. Twenty-four percent of the patients had multiple food allergies and had more common antibiotic use (41.9% vs 11.8%), atopic dermatitis (21% vs 10.2%), wheezing (11.3% vs 1.5%), colic (33.8% vs 11.2%), and IgE sensitization (50% vs 13.5%) compared to the single-food allergic group ( P < 0.001, P = 0.025, P = 0.003, P < 0.001, respectively). In multivariate logistic regression analysis, presence of colic (odds ratio [OR]: 5.128, 95% confidence interval [CI]: 1.926–13.655, P = 0.001), IgE sensitization (OR: 3.964, 95% CI: 1.424–11.034, P = 0.008), and having allergy to multiple foods (OR: 3.679, 95% CI: 1.278–10.593, P = 0.001] were found to be risk factors for continuing disease after 1 year of age. Conclusion: Although most children achieve tolerance at 1 year of age, IgE sensitization, allergy to multiple foods, and presence of colic were risk factors for persistent course and late tolerance. In this context, these children may require more close and extended follow-up. Abstract : Supplemental Digital Content is available in the text